Isolation and in vitro screening of the probiotic potential of microorganisms from fermented food products - Ntiantiasi, Nikoleta; Lianou, Alexandra (Frontiers in Industrial Microbiology, 2023)
Introduction Several human health benefits have been ascribed to probiotics, while traditional fermented foods have been acknowledged as rather important sources of these microorganisms. The objective of this study was the isolation of microorganisms from fermented food products of both animal and plant origin and the evaluation of their probiotic potential. Methods Microbial isolation was performed from milk kefir and table olives, while an olive mill waste sample also was analyzed given its anticipated association with the autochthonous microbiota of olive drupes. Among the 16 macroscopically distinct recovered microorganisms, 14 microbial isolates were identified as presumptive lactic acid bacteria (LAB), whereas two isolates corresponded to yeasts. The microbial isolates exhibiting a reproducibly robust growth profile in appropriate culture broth media (11 out of the 16 isolates) were assessed for their probiotic potential based on a set of in vitro assays: resistance to low pH; autoaggregation; biofilm formation; antioxidant activity; and safety assessment through evaluation of hemolytic activity. Results and discussion Based on the collective evaluation of the results of the abovementioned assays, five presumptive LAB as well as the two yeast isolates were identified as exhibiting desirable in vitro probiotic traits. Hence, these microbial isolates could be regarded as good candidates for inclusion in further studies aiming, ultimately, at their potential utilization in novel functional food products.